PENGARUH TERPAAN SOCIAL MEDIA MARKETING TERHADAP NIAT PENGGUNAAN BERKELANJUTAN MELALUI PERSEPSI HARGA: STUDI PADA PENGGUNA GORIDE HEMAT DAN GRABBIKE HEMAT - Davina Louisa Fey; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Ride-hailing services in Indonesia operate in a relatively homogeneous market with high price transparency, allowing users to compare fares, promotions, and service availability before booking. This multi-homing behavior makes usage decisions more situational and encourages platforms to emphasize price-oriented messages on social media. In this context, GoRide Hemat and GrabBike Hemat are both promoted as low-cost, affordable, and consistent services. This study aims to analyze the influence of social media marketing exposure on continuance intention, both directly and indirectly through price perception, and to describe the patterns found in both services. This research applies an explanatory quantitative approach using a survey of 160 respondents selected through purposive sampling. Social media marketing exposure was measured through attention and unaided recall, price perception through price acceptability, affordability, and price competitiveness, while continuance intention was measured through continued use, usage preference, and future use intention. The data were analyzed using PLS-SEM with SmartPLS. The findings show that social media marketing exposure has a positive and significant influence on price perception in both services. Price perception also has a positive and significant influence on continuance intention. The direct influence of social media marketing exposure on continuance intention is significant for GoRide Hemat, but not significant for GrabBike Hemat. In addition, the indirect effect through price perception is significant in both services. These findings indicate that price-oriented messages on social media need to be supported by consistent actual prices in the application to strengthen price perception and encourage continuance intention.